EVALUATION OF ENVIRONMENTAL FRAGILITY AS A SUBSIDY FOR ENVIRONMENTAL MANAGEMENT IN THE RIBEIRAO DO BELTRAO - MS WATERSHED - Vick, Erivelton Pereira; Santos da Silva, Edson Rodrigo dos; Bacani, Vitor Matheus; Rocha Lima, Cesar Gustavo da [UNESP]; Peluco, Ariane Aparecida; Gradella, Frederico dos Santos; Decco, Hermiliano Felipe; Ribeiro de Oliveira, Vincler Fernandes; Ferreira Neto, Milto; Brito, Rafael Martins (Univ Estado Rio Janeiro, 2021)
The Ribeirao do Beltrao watershed has an area of 300 km(2), located inside the city of Selviria-MS, is marked by intense changes in the landscape resulting from changes in land use and coverage in the last thirty years. Two rural settlements are installed on the limits of the Ribeirao do Beltrao watershed, Sao Joaquim (35.14 km(2)) and Alecrim (12.7 km(2)). The objective of this work was to evaluate the environmental fragility, taking into account the relationship of variables such as soils, slope, rainfall intensity, priority areas for biodiversity conservation and land use and coverage. The methodological procedures adopted were the weighted overlap of these variables in GIS (Geographic Information System) environment. The results indicated that in the majority of the basin there is an average environmental fragility (45.7%) associated with pasture and forestry areas, with declines between 6% and 12%, followed by low environmental fragility (43.1%), concentrated in places with the presence of natural vegetation; very high (11.1%), correlated to floodplain areas that have complex dynamics and require conservative management, since these areas are found in the vast majority outside the areas of APPs (28.1 km(2)), and high (0.1%), which is incipient in the mapping performed.
Keywords: Potential Fragility; Geoprocessing; Map Algebra; Remote sensing; GIS